Intravenous pulse cyclophosphamide and steroids induce immunological and clinical remission in New‐incident and relapsing primary membranous nephropathy. Issue 1 (17th December 2017) - Kanigicherla, Durga Anil K; Hamilton, Patrick; Czapla, Krystyna; Brenchley, Paul EC
ABSTRACT: Aim: Primary membranous nephropathy is associated with progression to end stage renal diseasein some patients. Standard therapy with cyclical cyclophosphamide and corticosteroids can be associated with significant adverse effects. We aimed to assess immunological and clinical response with intravenous pulse cyclophosphamide and oral steroids in patients with severe nephrotic syndrome – in a prospective observational cohort study. Methods: A total of 17 consecutive patients (nine new‐incident and eight relapses) with severe nephrotic syndrome received monthly intravenous pulse cyclophosphamide and oral steroids after failure to achieve remission with supportive therapy. Immunosuppressive therapy was discontinued at 6 months or earlier if proteinuria regressed to <100 mg/mmol and patients were followed for 12 months. Achievement of partial remission was primary outcome; changes in clinical parameters and anti‐PLA2 R were secondary outcomes. Results: Dose of cyclophosphamide received was 5.4 g in New‐incident patients and 4.2 g in patients with relapses. All 17 patients achieved partial remission within 6 months: proteinuria improved from 656 to 102 mg/mmol at 6 months and 55 mg/mmol at 12 months ( P < 0.001); eGFR improved from 31 to 48 mL/min per 1.73 m 2 at 6 months and 45 mL/min per 1.73 m 2 at 12 months ( P < 0.05). Anti‐PLA2 R levels reduced from 244 to 10 U/L at 6 months and 10 U/L at 12 months ( P < 0.001). Two out of nine patients in the New‐incident group developed subsequent relapse. Cumulative doses of cyclophosphamide and steroids that patients received was about half of the standard regime. Conclusion: Pulse cyclophosphamide with oral steroids induced immunological and clinical partial remission at significantly reduced doses in primary membranous nephropathy. Summary at a Glance: This study, although small and uncontrolled, suggests that acceptable rates of remission in primary membranous nephropathy may be achieved using lower cumulative doses of cyclophosphamide compared with usually used current regimens.